PENGARUH EKUITAS MEREK (BRAND EQUITY) DAN LAYANAN PURNA JUAL (AFTER SALES SERVICE) TERHADAP KEPUASAN CUSTOMER DAN DAMPAKNYA PADA LOYALITAS MEREK KASUS PADA EXCAVATOR KOBELCO - Mulyadiyanto Sumarsana, 12.5202.0174; Santosa, Eric (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose ofthe studyisto analyzeanddescribethe effect ofbrandequityandsales serviceon brand loyaltywithcustomersatisfactionas amediatingvariablein thecustomerKobelcoExcavator. The populationin this studyis thecustomerwhopurchasedthe unitKOLBECOExcavator. The analytical toolusedismultiple linear regression. The resultsofthis studyit can be concludedthat thepositive effectof brandequityonconsumersatisfaction, after sales servicehas positive influence onconsumersatisfaction, positive effect on thebrand equitybrand loyalty, after-salesservicehas positive influence onbrand loyalty, customersatisfactionhas positive influence onbrand loyalty, satisfactioncustomermediatesthe effect ofbrand equityoncustomerloyaltyto thebrandExcavatorKobelco, customersatisfactiondoes notmediatethe effect ofafter-sales servicetothecustomerbrand loyaltyKobelcoExcavator. Keywords: brand equity, after-sales service, customersatisfaction, brand loyalty